Radiocesium concentrations in wild boars captured within 20 km of the Fukushima Daiichi Nuclear Power Plant - Cui, Limeng; Orita, Makiko; Taira, Yasuyuki; Takamura, Noboru (Scientific reports, 2020)
The Fukushima Daiichi Nuclear Power Plant (FDNPP) accident in 2011 released large amounts of artificial radioactive substances into the environment. In this study, we measured the concentration of radiocesium ( 134 Cs + 137 Cs) in 213 muscle samples from wild boars ( Sus scrofa ) captured in Tomioka town, which is located within 20 km of the FDNPP. The results showed that 210 (98.6%) muscle samples still exceeded the regulatory radiocesium limit (100 Bq/kg) for general foods. Radiocesium ( 134 Cs + 137 Cs) levels ranged from 87.1–8,120 Bq/kg fresh mass (FM), with a median concentration of 450 Bq/kg FM. The median committed effective dose was estimated to be 0.070–0.26 μSv/day for females and 0.062–0.30 μSv/day for males. The committed effective dose for one-time ingestion of wild boar meat could be considered extremely low for residents in Tomioka. The relatively high levels of radioactivity found in this study suggest that the high variability of food sources may have led to the large accumulation of radioactive substances. These results suggest that comprehensive long-term monitoring is needed to identify risk factors affecting recovery from a nuclear disaster.